2019
DOI: 10.28982/josam.596891
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographically marked catheterization of internal jugular vein in intensive care patients: Retrospective cohort study

Abstract: Aim: This study was designed to compare the method of internal jugular vein (IJV) catheterization with prior ultrasonographic (USG) skin marking with the conventional method regarding the performance of a less experienced practitioner in learning ultrasonographic manipulation and safely performing the cannulation. Methods: The records of patients admitted to the Intensive Care Unit of Ataturk Chest Diseases and Chest Surgery Research and Training Hospital between April and September 2018 were retrospectively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In general, the interventional radiologists perform the procedure under ultrasonographic and fluoroscopic guidance and prefer the right internal jugular vein as the first choice for venous access. It has been indicated that TIVAP insertion under imaging guidance reduces the procedure-related complication rates [18][19][20]. On the other hand, surgeons use either cut-down or percutaneous landmark-based technique for implantation, with low complication rates [2,[7][8][9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the interventional radiologists perform the procedure under ultrasonographic and fluoroscopic guidance and prefer the right internal jugular vein as the first choice for venous access. It has been indicated that TIVAP insertion under imaging guidance reduces the procedure-related complication rates [18][19][20]. On the other hand, surgeons use either cut-down or percutaneous landmark-based technique for implantation, with low complication rates [2,[7][8][9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%